PENGARUH DANA PIHAK KETIGA (DPK), FINANCING TO DEPOSIT RATIO (FDR) DAN INFLASI TERHADAP PEMBIAYAAN USAHA KECIL DAN MENENGAH (UKM) PADA BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) DI PROVINSI RIAU - Anggia, Yanti Rahmi; Rosyetti, Rosyetti; Nobel, Aqualdo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
The purpose of this research is to know and significance the influence of Third Party Fund (DPK), Financing to Deposit Ratio (FDR) and Inflation on the financing of small and medium Enterprises (SMEs) in Islamic People’s financing banks (BPRS) in Riau Province in 2009-2019.The data used in this study are secondary time series. The analytical method used is multiple linear regression. The result of analysis shows that simultaneously the Third Party Fund (DPK), Financing to Deposit Ratio (FDR) and Inflation of have significant influence to the financing of small and medium Enterprises (SMEs) in Islamic People’s financing banks (BPRS) in Riau Province in 2009-2019. Partial test shows that Third Party Fund (DPK) have a positive and significant influence to the financing of small and medium Enterprises (SMEs) in Islamic People’s financing banks (BPRS) in Riau Province in 2009-2019. Financing to Deposit Ratio (FDR) have a positive and significant influence to the financing of small and medium Enterprises (SMEs) in Islamic People’s financing banks (BPRS) in Riau Province in 2009-2019. And Inflation have a positive and insignificant influence to the financing of small and medium Enterprises (SMEs) in Islamic People’s financing banks (BPRS) in Riau Province in 2009-2019.Keywords: Third Party Fund (DPK), Financing to Deposit Ratio (FDR), Inflation and financing of small and medium Enterprises (SMEs)